Photoionization of Nb3CO and Nb3(CO)2: Is CO molecularly or dissociatively adsorbed on niobium? - Pedersen, D.; Rayner, D.; Simard, B.; Addicoat, M.; Buntine, Mark; Metha, G.; Fielicke, A. (American Chemical Society, 2004)
The photoionization efficiency spectra of gas-phase Nb3CO and Nb3(CO)2 have been acquired using a laser-ablation, photoionization mass spectrometer. The adiabatic ionization energies of the species are 5.82 ± 0.02 and 5.85 ± 0.02 eV, respectively, where error bars reflect precision; the values are accurate to within 0.1 eV. From these data and literature values of cation bond strengths, the bond energies of Nb3−CO and Nb3CO−CO are found to lie within the 2.8−3.4 and 1.7−1.8 eV ranges, respectively. The former is most consistent with dissociatively adsorbed CO, while the latter may correspond to molecularly or dissociatively adsorbed CO. These conclusions are supported by density-functional theory calculations. In addition to properties of Nb3CO, the properties of the transition state to dissociative adsorption of CO have been calculated. It is found that the transition state lies lower in energy than the separated reagents. Spontaneous dissociation is expected to follow molecular adsorption of CO on Nb3, accordingly. Over the 1540−2220 cm-1 range, no infrared multiphoton dissociation of Nb3CO or Nb3(CO)2 is observed, consistent with CO being dissociatively adsorbed for both species.